2020
DOI: 10.17763/1943-5045-90.4.573
|View full text |Cite
|
Sign up to set email alerts
|

Nací Allá: Meanings of US Citizenship for Young Children of Return Migrants to Mexico

Abstract: In this essay, Joanna Dreby, Sarah Gallo, Florencia Silveira, and Melissa Adams-Corral use a transnational frame to explore the meanings of US citizenship for binational children and its importance to experiences of belonging. Drawing on interviews with children ages six to fourteen living with their Mexican-born parents in rural Puebla, their analysis shows that children view US citizenship as signaling their social location in a historically based migratory system and that the meaning of this social location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It is estimated that there are at least 600,000 transborder students with US schooling experiences enrolled in Mexican schools (Jacobo and Jensen 2018). These students are a relatively invisible population, and Mexican schooling offers limited support for transborder students who bring different knowledges and linguistic skills (Bybee et al 2020;Dreby et al 2020;Kleyn 2017;Gándara 2020;Zúñiga et al 2008).…”
Section: Schooling Across Bordersmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that there are at least 600,000 transborder students with US schooling experiences enrolled in Mexican schools (Jacobo and Jensen 2018). These students are a relatively invisible population, and Mexican schooling offers limited support for transborder students who bring different knowledges and linguistic skills (Bybee et al 2020;Dreby et al 2020;Kleyn 2017;Gándara 2020;Zúñiga et al 2008).…”
Section: Schooling Across Bordersmentioning
confidence: 99%
“…Research on critical consciousness has shown that young people who have experienced structures of inequity, such as racial discrimination in the U.S., often demonstrate more nuanced critical consciousness development compared with their mainstream peers who often benefit from systems of privilege (Diemer and Li 2011;Kelly 2016;Seaton 2010;Seider et al 2019). In previous collaborative work (Dreby et al 2020), we explored the perspectives of transborder students attending elementary school in Mexico and highlighted the ways that their experiences with migration status shaped their understandings of inequity and how they managed this among peers. Research has demonstrated how critical consciousness development among marginalized students can serve as a protective factor against further marginalization by supporting them to engage in critical reflection and collective action to "overcome pervasive myths" (Cervantes-Soon et al 2017, p. 419), blaming marginalized populations to instead center alternative histories revealing how hegemonic structures created oppressive conditions (Cammarota 2007;Ginwright 2010).…”
Section: Critical Consciousness Researchmentioning
confidence: 99%
“…Aaron was a transborder thinker, whose ways of knowing hold potential to be leveraged in schooling if they are intentionally recognized and built upon (Dyrness and Abu El Haj 2020). Instead, Aaron often felt excluded for not embodying local, mononational ways of knowing and struggled to get used to a new way of schooling that discounted his assets (see also Dreby et al 2020). Border pedagogies "bring together interrogations of the self (identity, agency) and others (culture, society, structures), to examine one's position, how it is "read," and how it relates to power in the word and the world by encouraging each individual to locate her or his identity within particular histories of power, colonization, imperialism, and difference" (Cervantes-Soon et al 2017, 419).…”
Section: Envisioning Border Pedagogiesmentioning
confidence: 99%